Pengembangan Media Interaktif Canva untuk Meningkatkan Kemampuan Pronunciation Siswa SD Muhammadiyah 8 Banjarmasin - Shahana, Alya; Mansur, Hamsi; Ratumbuysang , Monry Fraick Nicky (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to develop and evaluate the effectiveness of Canva-based interactive PowerPoint media to enhance pronunciation skills among fifth-grade students at SD Muhammadiyah 8 Banjarmasin. Employing a Research and Development (R&D) methodology with a 4D model (Define, Design, Develop, Disseminate), the research identifies specific learning needs, designs prototypes, validates media through expert reviews, and implements it in the classroom. Observations revealed challenges such as limited vocabulary, pronunciation difficulties, and monotonous teaching methods relying on textbooks and audio recordings. The developed media combines visual, audio, and interactive elements, including quizzes, to engage students. Validation results showed high feasibility, with expert ratings averaging over 98%. A trial with 19 students demonstrated a significant improvement in pronunciation, with an average pre-test score of 62.36 increasing to 83.84 in the post-test, supported by an N-Gain of 0.50 (medium effectiveness). Feedback from teachers and students indicated that the media was practical, visually appealing, and motivational. The findings suggest that Canva-based interactive PowerPoint media effectively addresses pronunciation challenges while enhancing student engagement and learning outcomes. This research highlights the transformative potential of integrating digital tools into education, offering practical solutions for language learning at the elementary level